Intervensi yang Mendukung Kualitas Hidup Penyintas Tumor Otak - Renie Kumalasari; Dewi Gayatri; Yati Afiyanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Based on previous studies ' results, this study aims to examine interventions that impact brain tumor survivors' quality of life. The method used is a literature study. Article search through Science Direct, Pubmed, and Google Scholar databases. The search keywords are brain tumor, QOL, RCT, and Intervention. The Boolean logic used is